Screening attendance disparities among Hungarian-speaking Roma and non-Roma women in central and eastern European countries - Mózes, Noémi; Takács, Johanna; Ungvari, Zoltan; Feith, Helga Judit (Frontiers in Public Health, 2023)
The Roma populations in Central and Eastern Europe are two to three times more likely to have unmet health needs compared to non-Roma residents. The aim of the present study was to investigate the disparity in screening attendance frequency between Hungarian-speaking Roma (R) and non-Roma (nR) women in Hungary (HU-R:322; nR:294), Romania (RO-R:258; nR:183), and Slovakia (SK-R:146; nR:163), while also identifying the factors that influence attendance at any kind of screening tests in both populations. In order to examine these factors, a multivariate multiple binary logistic regression was conducted. The findings revealed significant associations between attendance at any kind of screening tests and certain factors among different groups.Among Hungarian Roma women, it was found that having a chronic disease and smoking were linked to attendance at any kind of screening tests (p=0.009). Specifically, having a chronic disease increased the odds of attendance (OR=1.71[1.01;2.90]), while smoking decreased the odds (OR=0.57[0.365;0,91]). In Romania, the study found that not having health insurance decreased the odds of attendance among Roma women (OR=0.50[0.27;0.91]), whereas having a chronic disease increased the odds (OR=2.87 [1.44;5.72]) (p=0.006). Among non-Roma women in Romania, physical inactivity was associated with a decreased likelihood of attendance at any kind of screening tests (OR=0.48[0.25;0.95]). Among Slovakian Roma women, not having health insurance (OR=0.09[0.02;0.36]) and smoking (OR=0.25[0.11;0.61]) were found to decrease the odds of attendance (p<0.001). On the other hand, non-Roma women in Slovakia with chronic diseases were more likely to attend at any kind of screening tests (OR=2. 52[1.12;5.66]). Our research emphasizes the impact of lacking health insurance on screening attendance, particularly among the Roma population. It also highlights the significance of health-related behaviours such as smoking and physical inactivity in relation to missed screening s tests, which in turn contribute to the development of non-communicable diseases. Therefore, promoting targeted screening programs for the Roma community is crucial to ensure their access to screenings tests, especially in cases of chronic illnesses.